1996
DOI: 10.1007/bf02088756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omeprazole on movement of intravenously administered metronidazole into gastric juice and its significance in treatment ofHelicobacter pylori

Abstract: Four healthy, Helicobacter-negative volunteers were studied to determine the effect of omeprazole on the movement of metronidazole across the gastric mucosa into the gastric lumen. Each received a 500-mg intravenous infusion of metronidazole and repeated serum, and gastric juice samples were obtained concomitantly over an 8-hr study via indwelling intravenous catheter and nasogastric tube. The same protocol was repeated following one week of oral omeprazole 20 mg twice daily. Metronidazole concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Theoretically, one can therefore expect that higher gastric metronidazole levels can be achieved if higher doses of metronidazole are given in combination with PPIs. This study, however, indicates that there is little therapeutic gain when using higher doses of metronidazole, although gastric juice metronidazole levels were not measured [10,11]. It remains to be determined whether a course of treatment longer than a week will overcome the effect of resistance and improve outcome.…”
Section: Discussionmentioning
confidence: 71%
“…Theoretically, one can therefore expect that higher gastric metronidazole levels can be achieved if higher doses of metronidazole are given in combination with PPIs. This study, however, indicates that there is little therapeutic gain when using higher doses of metronidazole, although gastric juice metronidazole levels were not measured [10,11]. It remains to be determined whether a course of treatment longer than a week will overcome the effect of resistance and improve outcome.…”
Section: Discussionmentioning
confidence: 71%
“…The antimicrobial effect of many compounds, including bismuth (33), tetracycline (33), amoxicillin (14), and clarithromycin (10), is reduced under acidic conditions. In contrast, metronidazole has been found to be chemically stable under a wide range of pH values (39).…”
Section: Vol 47 2003 H Pylori Treatment Failures and The Transitiomentioning
confidence: 97%
“…The reduced inflammation in mice compared to humans may be one explanation for the high success rate of monotherapy with metronidazole. There are convincing data in the literature that demonstrate that metronidazole can cross the gastric mucosa (13,39). This may improve the success rate with this medication.…”
Section: Vol 47 2003 H Pylori Treatment Failures and The Transitiomentioning
confidence: 97%
“…Metronidazole doses of 500 mg produce mean peak levels in plasma of 11.5 mg/ml, and the metronidazole half-life is 8 h (22). Veldhuyzen van Zanten et al (28) found the metronidazole concentration to be much higher in gastric fluid than in plasma. In the present study, the incubation times and the drug concentrations were chosen according to the half-lives and the clinically achievable concentrations of clarithromycin (5), metronidazole (22), and tinidazole (22).…”
Section: Discussionmentioning
confidence: 99%